An advanced guide to trade policy analysis : the structural gravity model - Yotov, Yoto V.; World Trade Organization (Geneva : World Trade Organization, 2016)
"This Advanced Guide has been developed to contribute to the engancement of developing countries' capacity to analyse and implement trade policy. It is aimed at government experts engaged in trade negotiations, as well as graduate students and researchers involved in trade-related study or research"--Page 4 cover.
Includes bibliographical references (pages 131-137).
Keywords: Commercial policy; International economic relations